2021
DOI: 10.1192/j.eurpsy.2021.1781
|View full text |Cite
|
Sign up to set email alerts
|

A study on patterns of use of mobile phone and nomophobia in medical undergraduate students during a COVID-19 pandemic lockdown

Abstract: IntroductionThe governments of various countries enforced a lockdown to contain the COVID -19 pandemic. As the colleges remain closed, the academic teachings for students was conducted online. The mobile phone remained the main source for academics and entertainment during this period.ObjectivesTo assess patterns of use of mobile phone by Medical Undergraduate students prior to and during the COVID-19 lockdown. To assess Nomophobia among same participants.MethodsThis study was done by an online survey method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Various studies have been conducted during the global health crisis on nomophobia: For instance, Bhatnagar et al (2021) assessed nomophobia prior to and during the COVID-19 lockdown, reporting an increase of smartphone overuse during the pandemic restrictions, with a significant proportion of participants with moderate to severe nomophobic symptoms, whereas Sui et al (2022) indicated that nomophobic symptoms tend to be stable when compared with pre-pandemic data; also, Zwilling (2022) showed that nomophobic levels, along with their repercussions on problematic smartphone use, increased from the beginning of the first COVID-19 wave (T1) to the end of the COVID-19 lockdown (T2), highlighting how the addictive outcomes endure longer, even when the pandemic was less widespread; further, Nguyen et al (2022) investigated the effects of nomophobia on stress, also testing the indirect path through loneliness, indicating that the perception of feeling lonely may increase stress in individuals who show nomophobic symptoms.…”
Section: Nomophobia During the Pandemicmentioning
confidence: 99%
“…Various studies have been conducted during the global health crisis on nomophobia: For instance, Bhatnagar et al (2021) assessed nomophobia prior to and during the COVID-19 lockdown, reporting an increase of smartphone overuse during the pandemic restrictions, with a significant proportion of participants with moderate to severe nomophobic symptoms, whereas Sui et al (2022) indicated that nomophobic symptoms tend to be stable when compared with pre-pandemic data; also, Zwilling (2022) showed that nomophobic levels, along with their repercussions on problematic smartphone use, increased from the beginning of the first COVID-19 wave (T1) to the end of the COVID-19 lockdown (T2), highlighting how the addictive outcomes endure longer, even when the pandemic was less widespread; further, Nguyen et al (2022) investigated the effects of nomophobia on stress, also testing the indirect path through loneliness, indicating that the perception of feeling lonely may increase stress in individuals who show nomophobic symptoms.…”
Section: Nomophobia During the Pandemicmentioning
confidence: 99%